Land scarcity impedes sustainable input intensification in smallholder irrigated agriculture: Evidence from Egypt - Abay, Kibrom A.; El-Enbaby, Hoda; Abdelfattah, Lina Alaaeldin; Breisinger, Clemens (International Food Policy Research Institute, 2021)
Increasing population pressure and population density in many African countries are inducing land scarcity and land constraints. These increasing land constraints are expected to trigger various responses and adaptation strategies, including agricultural intensification induced by land scarcity, as postulated by the Boserup hypothesis. However, most empirical evaluations of the Boserup hypothesis come from rainfed agriculture and mostly from Sub-Saharan Africa (SSA), where application of improved agricultural inputs remains historically low. Agricultural intensification practices as well as the relevance of the Boserup hypothesis in irrigated agriculture and in contexts where application of improved inputs is high remains unexplored. Furthermore, while much of the debate on the topic in Africa has focused on how to boost agricultural intensification, there is scant evidence on whether evolving agricultural intensification practices in some parts of Africa are sustainable, yield-enhancing, and optimal. In this paper we investigate the implication of land scarcity on agricultural intensification and the relevance of the Boserup hypothesis in the context of Egypt, where agriculture is dominated by irrigation and input application rates are much higher than SSA. We also examine whether evolving agricultural intensification practices induced by land scarcity are agronomically appropriate and yield-enhancing. We find that land scarcity induces higher application of agricultural inputs, mainly nitrogen fertilizers, sometimes beyond the level that is agronomically recommended. More importantly, land scarcity increases overapplication of nitrogen fertilizer relative to crop-specific agronomic recommendations. This implies that land constraints remain as important challenges for sustainable agricultural intensification. Finally, we find suggestive evidence that such overapplication of nitrogen fertilizers is not yield-enhancing, but, rather, yield-reducing. We also document that land scarcity impedes mechanization of agriculture. Our findings have important implications to inform appropriate farm management and sustainable intensification practices. Furthermore, our results can inform long-term responses to land scarcity.